Discovery Nusantara Creative Dance Creation Training as a Platform for Talent Development and Social Therapy for Inmates at Kerobokan Women's Prison - Agustawan, Dewa Made; Putra, I Gede Gunadi; Widyastuti, Ida Ayu Gede Sasrani (Outline Journal of Community Development, 2025)
This community service activity aims to provide training in creating the creative dance "Discovery Nusantara" as a means of developing talent, increasing self-confidence, and social therapy for children in Kerobokan Women's Prison. The implementation method of this service activity uses a participatory approach by actively involving the inmates in the process of creating, practicing, and performing the dance. In addition to being a means of entertainment, this activity also serves as a forum for developing the interests and talents of the inmates of Kerobokan Prison. The results of the activity show that there is an increase in motor skills, creativity, and social interaction of participants when participating in the creation, practice, and performance sessions. This activity also contributes to building and strengthening local cultural values ​​and broadening the participants' artistic and cultural insights.